A cluster of Psittacosis cases in Lishui, Zhejiang Province, China, in 2021 - Yao, Wenwu; Chen, Xiuying; Wu, Zhuoying; Wang, Lingbo; Shi, Guoxiang; Yang, Zhangnv; Zhang, Yanjun; Wu, Beibei (Frontiers in Cellular and Infection Microbiology, 2022)
Psittacosis, caused by Chlamydia psittaci (C. psittaci), are wide spread throughout the world. The C. psittac infection in humans may lead to severe conditions and complications, including sepsis and multiple organ failure. We report a disease outbreak caused by Chlamydia psittaci in Zhejiang Province, 2021, which led to one death and three cases of hospitalization. The cases were confirmed by nest-PCR, RT-PCR and mNGS. The four cases were connected and the sequences obtained from these samples were closely related to those from Taiwan. This is the first to report on the case of death from psittacosis in Zhejiang Province, and our study may help assess the disease and recommend effective measures to prevent further spread of C. psittaci.